New perspectives on autism: two equations to describe a complex disorder and envisage new treatments - B. Suare; M.-A. Jeune (Акушерство, гинекология и репродукция)
Autism spectrum disorder (ASD) is a neurodevelopmental condition that can be reliably diagnosed in children by age 18–24 months. Prospective longitudinal studies of infants aged 1 year and younger who are later diagnosed with autism are elucidating the early developmental course of autism and identifying ways of predicting autism before diagnosis is possible. Studies that use magnetic resonance imaging and electroencephalography, have identified differences in brain development in infants later diagnosed with autism compared with infants without autism. Retrospective studies of infants younger than 1 year who received a later diagnosis of autism have also showed an increased prevalence of health conditions, such as sleep disorders, gastrointestinal disorders, and vision problems. We propose two equations to describe this complex disorder: the first indicates the factors at the origin of the disease, the second synthesizes the different factors leading to a more or less severe disease. Although research findings offer insight on promising screening approaches for predicting autism in infants, individual-level predictions remain a future goal. Multiple scientific challenges and ethical questions remain to be addressed to translate research on early brain-based and behavioural predictors of autism into feasible and reliable screening tools for clinical practice.